Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1016/j.femsle.2005.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Osmotically induced trehalose and glycine betaine accumulation improves tolerance to desiccation, survival and efficacy of the postharvest biocontrol agentPantoea agglomeransEPS125

Abstract: The application of the biocontrol agent Pantoea agglomerans EPS125 to unwounded fruits was practically ineffective for control of postharvest blue mould caused by Penicillium expansum when the treatment and subsequent wounding and pathogen inoculation were separated by periods of unfavourable conditions. This was due to a rapid decrease in viability of the alocthonous introduced biocontrol agent in the intact peel surface. A system for osmoadaptation of the biocontrol agent was developed by combining saline os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 36 publications
2
30
1
Order By: Relevance
“…This result could be attributed to the environment of the wound, which may protect the antagonist yeast against the adverse effects of environmental factors or by the time elapsing between the antagonist application and pathogenic inoculation. This result was unlike Lahlali et al (2008) and Bonaterra et al (2005), who reported a significant effect of environmental factors (temperature and relative humidity) when the BCA was applied directly on the fruit surface. However, with P. guilliermondii, the temperature and RH have proven to have a highly significant effect on the lesion diameter of P. italicum.…”
Section: Discussioncontrasting
confidence: 88%
“…This result could be attributed to the environment of the wound, which may protect the antagonist yeast against the adverse effects of environmental factors or by the time elapsing between the antagonist application and pathogenic inoculation. This result was unlike Lahlali et al (2008) and Bonaterra et al (2005), who reported a significant effect of environmental factors (temperature and relative humidity) when the BCA was applied directly on the fruit surface. However, with P. guilliermondii, the temperature and RH have proven to have a highly significant effect on the lesion diameter of P. italicum.…”
Section: Discussioncontrasting
confidence: 88%
“…In order to be successful, the inoculum of BCA should tolerate various environmental stresses of the orchard, including higher temperatures, lower water availability, low nutrients and ultraviolet radiations (Teixidõ et al, 1999). Bonaterra et al (2005), reported that the application of Pantoea agglomerans to unwounded fruits was practically ineffective for controlling the blue mold when the biological treatment, subsequent wounding and pathogen inoculation were separated by long periods of low relative humidity conditions. The authors attributed the lack of efficacy to the difficulties in colonization and survival of antagonistic bacteria in the intact peel surface compared to the rapid growth observed in fresh wounds.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial amount of research has been conducted on improving the resistance of BCA to abiotic stress by adaptation of growth to unfavorable osmotic conditions (Bonaterra et al, 2005). In this study, we were interested in an exogenous approach focused on the application of some protectant additives in combination with the BCA to improve its tolerance to environmental stress and, therefore, promote their establishment on apple fruit surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially the case for the well-studied soil bacterium Bacillus subtilis (4). This organism can synthesize GB from exogenous choline but makes little GB upon growth in minimal media (3,4). However, B. subtilis has a number of systems for GB uptake, and it is likely that GB and other osmolytes derived from root or animal exudates and dying cells of both eukaryotes and prokaryotes are present in soils and other environmental niches (4,12,26).…”
mentioning
confidence: 99%
“…GB appears to be the most effective osmolyte in growing B. subtilis cells, and it can accumulate to Ն500 mM (12,27). In addition to providing osmoprotection to growing B. subtilis cells, GB can also provide significant thermal protection (12) and has been reported to provide desiccation resistance to bacteria of a number of genera (3,5).…”
mentioning
confidence: 99%